FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SEPATU DI TOKO FAJAR SPORT KECAMATAN PEDURUNGAN KOTA SEMARANG - Idris, Fajar; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2015)
This research aims to test the effect of promotions, price perception, quality of service, and location on the purchasing decision on Fajar Sport. Drop in sales experienced by the Fajar Sport background problem in this research.In this research using a method of collecting data with a questionnaire with the number of samples 100 respondents, the sample accidental use sampling techniques and methods of analysis of data used in this research is linear regression worship of idols.The result of this research shows that all the independent variable that is a promotion, price perception, the quality of service, location has links positive in line against the dependent variable for which is purchasing decisions. The testing of hypotheses using test t show that the four independent variable for which researched proved to be significantly affect the decision purchase. Then through the f can be known that in the fourth joint of a variable that affected decision purchase. Figures adjusted r square worth 0,654 show that the independent variable can explain65,4% decision the purchase of the remaining 34,6% by other variables out of one variable are used in this research